2023
DOI: 10.5812/pedinfect-134518
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Colonization with Carbapenem-resistant Enterobacteriaceae, Escherichia coli, Klebsiella and Enterobacter, and Related Risk Factors in Children

Abstract: Background: Carbapenems are broad-spectrum antibiotics used to treat the family of gram-negative Enterobacteriaceae, especially those that are resistant to first-line antibiotics. Because these drugs are usually prescribed as the last line of treatment, resistance to these antibiotics carries irreparable risks to treatment systems, and screening high-risk individuals in medical centers and using infection control measures are critical strategies for eliminating them. Objectives: We investigated the prevalence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
2
1
1
Order By: Relevance
“…In Ghana, Owusu et al ( 2023) reported these similar findings, where E. coli and K. pneumoniae were the predominant GNB species at 46% (n=83) and 17% (n=30), respectively. Furthermore, studies conducted in other countries have reported both same species with the most carbapenem-resistant strains (Haji et al, 2021;Armin et al, 2023). The results are in agreement with the study in Burkina Faso by Kabore et al (2022) who reported that GNB is mainly more resistant to antibiotics including carbapenems were E. coli and K. pneumoniae, but at higher rate (82.69%) and lower rate (9.62%) respectively.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In Ghana, Owusu et al ( 2023) reported these similar findings, where E. coli and K. pneumoniae were the predominant GNB species at 46% (n=83) and 17% (n=30), respectively. Furthermore, studies conducted in other countries have reported both same species with the most carbapenem-resistant strains (Haji et al, 2021;Armin et al, 2023). The results are in agreement with the study in Burkina Faso by Kabore et al (2022) who reported that GNB is mainly more resistant to antibiotics including carbapenems were E. coli and K. pneumoniae, but at higher rate (82.69%) and lower rate (9.62%) respectively.…”
Section: Discussionsupporting
confidence: 89%
“…These findings are comparable to those reported in Iraq, where detection rate of blaIMP gene was 43% (n=23/53) in clinical GNB strains, and this gene most prevalent in Escherichia coli (50%) (Haji et al, 2021). Our carbapenemase-IMP gene frequency (35.2%, n=32/91) was highest than those recorded in previous studies in Sudan (26.4%) (Adam et Elhag, 2018), in Egypt (11.8%) (Abbas et al, 2019) and in Iran (13%) (Armin et al, 2023). This increasing detection rate of blaIMP comparing to frequencies of these previous studies would suggested a currently worrying spread of carbapenem-resistant GNB producing IMP-type carbapenemase (Li et al, 2023).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…A significant fraction of these infections result in death due to limited treatment options [ 1 , 22 , 30 , 44 ]. Specifically, bloodstream infection by CRE causes a high mortality rate in pediatric populations [ 40 , 45 ]. The characteristics, mechanisms, and outcomes of carbapenem-resistant bacteria are thus crucial to prevent and manage such infections [ 46 ].…”
Section: Urgent Threat Of Infections By Antimicrobial Resistant Bacte...mentioning
confidence: 99%